2013
DOI: 10.14569/ijacsa.2013.041105
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison between Naïve Bayes, Decision Tree and k-Nearest Neighbor in Searching Alternative Design in an Energy Simulation Tool

Abstract: Abstract-Energy simulation tool is a tool to simulate energy use by a building prior to the erection of the building. Commonly it has a feature providing alternative designs that are better than the user's design. In this paper, we propose a novel method in searching alternative design that is by using classification method. The classifiers we use are Naïve Bayes, Decision Tree, and k-Nearest Neighbor.Our experiments hows that Decision Tree has the fastest classification time followed by Naïve Bayes and k-Near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 23 publications
1
74
0
4
Order By: Relevance
“…Previous studies on algorithm of classification have proven that naïve bayes is the best algorithm in comparison with the other ones such of Decision Tree, Naïve Bayes, and K-NN [9]- [11]. It has also been found that accuracy and speed are the most supporting and helpful features of the algorithm in classifying data.…”
Section: Naïve Bayes Algorithmmentioning
confidence: 99%
“…Previous studies on algorithm of classification have proven that naïve bayes is the best algorithm in comparison with the other ones such of Decision Tree, Naïve Bayes, and K-NN [9]- [11]. It has also been found that accuracy and speed are the most supporting and helpful features of the algorithm in classifying data.…”
Section: Naïve Bayes Algorithmmentioning
confidence: 99%
“…The purpose of a prediction algorithm is to forecast future values based on our present records. [3] Some common tools for prediction include: neural networks, regression, Support Vector Machine (SVM), and discriminant analysis. Recently, data mining techniques such as neural networks, fuzzy logic systems, genetic algorithms and rough set theory are used to predict control and failure detection tasks [4].…”
Section: Prediction Algorithmmentioning
confidence: 99%
“…Decision tree falls under supervised learning techniques as we have known labels in the training data set in order to train the classifier [3]. The Traditional Algorithm for learning decision trees is implemented using information gain as well as using gain ratio.…”
Section: Decision Treementioning
confidence: 99%
See 1 more Smart Citation
“…Support Vector Machine and Naive Bayes Classifier are studied for various training sets and their efficiency for unknown set are analyzed for Accuracy, AUC [10], Error Rate, F-measure, Precision, Recall and Specificity [11].…”
Section: Introductionmentioning
confidence: 99%